1988
DOI: 10.1029/jc093ic09p10589
|View full text |Cite
|
Sign up to set email alerts
|

The response of the equatorial Pacific Ocean to a westerly wind burst in May 1986

Abstract: Western Pacific westerly wind bursts of 1‐ to 3‐week duration are potentially important in triggering and sustaining El Niño‐Southern Oscillation events. One such burst of 10‐day duration and maximum speeds of greater than 10 m s−1 occurred in May 1986 west of the date line. The response to this westerly wind burst is documented from equatorial current meter moorings, thermistor chain moorings, and sea level and hydrographic data. At 0°, 165°E in the western Pacific the thermocline was depressed by 25 m, sea s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
54
0

Year Published

1990
1990
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 126 publications
(57 citation statements)
references
References 29 publications
3
54
0
Order By: Relevance
“…With a depressed thermocline, as induced by such downwelling waves, and an advection of warm water associated with the accelerating eastward surface current, warming of upper ocean waters would be found downstream from the remote wind forcing region. Theoretical and observational studies also lend support for wind-generated c1990, Meteorological Society of Japan oceanic Kelvin pulses in the equatorial waveguide (e.g., Lukas et al, 1984;Inoue and O'Brien, 1984;Cane and Zebiak, 1985;McPhaden et al, 1988;Harrison and Giese, 1988). However, only under proper oceanic conditions can a sequence of bursts raise the sea surface temperature (SST) anomalies in the eastern Pacific.…”
Section: Introductionmentioning
confidence: 93%
“…With a depressed thermocline, as induced by such downwelling waves, and an advection of warm water associated with the accelerating eastward surface current, warming of upper ocean waters would be found downstream from the remote wind forcing region. Theoretical and observational studies also lend support for wind-generated c1990, Meteorological Society of Japan oceanic Kelvin pulses in the equatorial waveguide (e.g., Lukas et al, 1984;Inoue and O'Brien, 1984;Cane and Zebiak, 1985;McPhaden et al, 1988;Harrison and Giese, 1988). However, only under proper oceanic conditions can a sequence of bursts raise the sea surface temperature (SST) anomalies in the eastern Pacific.…”
Section: Introductionmentioning
confidence: 93%
“…Observations have shown that almost every El Niño in recent history was closely associated with the westerly wind bursts (WWBs) (McPhaden, 2004;Lian et al, 2014b;Chen et al, 2015), a type of high-frequency atmospheric perturbations over the western-central tropical Pacific (Harrison and Vecchi, 1997;Fu and Huang, 1997;Vecchi and Harrison, 2000;Yan and Zhang, 2002;Seiki and Takayabu, 2007). The WWBs could warm the central equatorial Pacific SST by advecting warm water eastward from the western Pacific warm pool, and produce SST warming in the eastern equatorial Pacific by generating downwelling Kelvin waves (McPhaden et al, 1988(McPhaden et al, , 1992McPhaden, 2004;Lian et al, 2014b;Fedorov et al, 2015). It was also suggested that WWBs could warm the equatorial Pacific by increasing the nonlinear interaction between surface wind and the SST anomaly (Rong et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…WWBs play an important role in the tropical climate (see the review in Lengaigne et al 2004). In particular, WWBs over the western and central equatorial Pacific can drive strong anomalous eastward sea surface currents that lead to the increase in the sea surface temperature (SST) in the central equatorial Pacific, and induce downwelling Kelvin waves within the equatorial wave guide which is crucial to the warm SST anomalies in the eastern tropical Pacific (McPhaden et al 1988;Lengaigne et al 2002Lengaigne et al , 2003. Thus, WWBs are regarded as a fundamental process for modulating the El Niño-Southern Oscillation (ENSO;McPhaden 1999;Vecchi and Harrison 2000).…”
Section: Introductionmentioning
confidence: 99%